Conversion of Waste Cooking Oil Combined With Corn Oil Into Biodiesel Using the Transesterification Method - Suardi; Faisal Mahmuddin; Syerly Klara; Wira Setiawan; Muhammad Uswah Pawara; Jumardi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
This research endeavors to explore a novel alternative fuel source by combining waste used cooking oil and corn oil to create a biodiesel blend. The study addresses two main objectives: first, to investigate the properties of used cooking oil biodiesel with the addition of methanol and NaOH catalysts, and second, to assess engine performance using the biodiesel blend. The experimental approach employs transesterification, varying the catalyst quantity during biodiesel production. Preceding diesel engine testing, properties such as viscosity are assessed, revealing improved values meeting Indonesian National Standards post-catalyst addition, albeit with a decrease in calorific value. Engine performance is then evaluated, demonstrating that as the catalyst content increases, torque and thermal efficiency decrease, while specific fuel consumption (SFC) rises. Notably, the study concludes that a higher catalyst ratio aligns fuel properties closer to government-set standards. The most favorable engine performance is observed in the B50 sample with a catalyst variation of 1000 ml of methanol and 25 g of NaOH, showcasing superior torque, thermal efficiency, and opacity values compared to higher catalyst variations. This research underscores the importance of catalyst optimization in achieving an environmentally friendly biodiesel blend with enhanced engine performance.